The Influence of Job Satisfaction and Job Insecurity on Employee Turnover Intention at Hotel Harmony in Kubu Raya Regency - Dea Maulydiawati; Arninda Arninda (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study analyzes the influence of Job Satisfaction and Job Insecurity on Turnover Intention among employees at Hotel Harmony in Kubu Raya Regency. The high rate of employee turnover causes various problems, such as increased recruitment costs, decreased service quality, and disruptions to hotel operations. The purpose of this research is to identify the factors affecting employees’ intentions to leave the company, focusing on two main variables: Job Satisfaction and Job Insecurity. A quantitative approach was used, employing a survey method with a structured questionnaire. The respondents consisted of 44 individuals selected using a non-probability sampling technique. Data analysis was conducted using multiple linear regression to determine both the simultaneous and partial effects between the variables. The F-test results indicate that Job Satisfaction and Job Insecurity simultaneously have a significant effect on Turnover Intention. The t-test shows that Job Satisfaction has a negative and significant effect, meaning that the higher the job satisfaction, the lower the intention to leave. Conversely, Job Insecurity has a positive and significant effect, indicating that a sense of job insecurity encourages the intention to leave. The coefficient of determination (R²) value of 0.639 shows that these two variables explain 63.9% of the variation in Turnover Intention. This study recommends that management improve job satisfaction by creating a comfortable work environment, establishing a fair reward system, and maintaining open communication. Additionally, management needs to foster a sense of security to reduce anxiety and suppress Turnover Intention.